Knock-Down of Specific Thyroid Hormone Receptor Isoforms Impairs Body Plan Development in Zebrafish - Lazcano, Iván; Rodríguez-Ortiz, Roberto; Villalobos, Patricia; Martínez-Torres, Ataúlfo; Solís-Saínz, Juan Carlos; Orozco, Aurea (Frontiers in Endocrinology, 2019)
Thyroid hormones (THs) are key regulators of development, growth and metabolism in all vertebrates. The role of THs in development has been extensively studied; however, the specific molecular mechanisms involved are far from being clear. THs act by binding to TH nuclear receptors that act as ligand-dependent transcription factors to regulate TH-dependent gene expression. Thus, TH-thyroid hormone receptor (TR) binding is the first step to regulate the genomic action of these endocrine messengers. Zebrafish, like the rest of vertebrates, express different isoforms of functional Tr alpha and beta, and some of the expressed isoforms can bind alternative ligands like 3,5-T2. In the present study, we generated crispants for four isoforms of thr to learn more about the role of these receptors in early development, as well as to analyze the expression of some early development genes and identify if they were direct thra- or thrb-mediated TH targets. We found that larvae from thraa and l-thrb1+ crispants showed profound deleterious effects upon symmetry and lateralization, suggesting early novel roles for these Tr isoforms in the body plan development program. We also explored the expression of early development genes known to be involved in symmetry and lateralization in thr crispants and identified at least two direct thra- or thrb-mediated TH target genes. These results suggest a novel role for TRs in body plan during development.